(untitled) (Bangladesh Journal of Endosurgery, 2013)
We present a unique case of a 10-year-old girl who was a known case of congenital heart disease. She underwent Rastelli procedure twice for the same problem, but developed pericardial effusion in the postoperative period following which pericardiocentesis was done. She developed recurrent pericardial and pleural effusion, was not responding to drainage and pleurodesis. The pericardial effusion was endangering the surgical outcome of the previous surgery. Since she had multiple entry site scars and repeated percardiocentesis with pleurodesis, thoracotomy with pericardiectomy seemed to be a less viable option. We subjected the patient to a minimally invasive method of treatment by doing a laparoscopic trans-diaphragmatic pericardiectomy. The details of the procedure and our experience with management of the case are highlighted. In cases of repeated pericardial effusion failing conservative management, laparoscopic pericardiectomy seems to be a less invasive and more viable option. DOI: http://dx.doi.org/10.11593/bje.2013.0102.0008 Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 20-22